2024
DOI: 10.1111/1365-2435.14526
|View full text |Cite
|
Sign up to set email alerts
|

Rapid positive response of young trees growth to warming reverses nitrogen loss from subtropical soil

Maokui Lyu,
Shidong Chen,
Qiufang Zhang
et al.

Abstract: Global warming is widely expected to alter nitrogen (N) cycling in terrestrial ecosystems by accelerating N transformations in soils. However, it is unclear how warming will affect plant–soil N cycling in subtropical ecosystems. Here, we measured the N transformations including net ammoniation, nitrification, nitrous oxide emissions and nitrate in soil solution throughout the plant–soil continuum with 2 years of experimental soil warming (+5°C) in a young subtropical Chinese fir mesocosm. Seasonal variations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 86 publications
(153 reference statements)
0
0
0
Order By: Relevance
“…Conversely, other studies have shown that warming negatively affects microbial biomass (Melillo et al, 2017), which could decrease the magnitude of PEs and even change their directionality (Zhang et al, 2021). Additionally, warming could increase soil nitrogen (N) availability by promoting N mineralization (Bai et al, 2013;Grant, 2014;Lyu et al, 2024), thereby alleviating microbial N limitation and inducing the negative response of PE to warming (i.e., microbial N mining hypothesis) (Craine et al, 2007;. Furthermore, warming stimulates microbial activity and speeds up the decomposition of organic matter and thus increases N mineralization when substrates are N rich but increases N immobilization when substrates are N poor.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, other studies have shown that warming negatively affects microbial biomass (Melillo et al, 2017), which could decrease the magnitude of PEs and even change their directionality (Zhang et al, 2021). Additionally, warming could increase soil nitrogen (N) availability by promoting N mineralization (Bai et al, 2013;Grant, 2014;Lyu et al, 2024), thereby alleviating microbial N limitation and inducing the negative response of PE to warming (i.e., microbial N mining hypothesis) (Craine et al, 2007;. Furthermore, warming stimulates microbial activity and speeds up the decomposition of organic matter and thus increases N mineralization when substrates are N rich but increases N immobilization when substrates are N poor.…”
Section: Introductionmentioning
confidence: 99%